Przedsiębiorstwo w projekcie części ogólnej kodeksu cywilnego Rzeczpospolitej Polskiej z lat 1928−1932 - Górnicki, Leonard (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The subject of analysis are the legal regulations on enterprise in the draft of the general part of the Civil Code of 1928–1932, whose author referent of the Codifi cation Committee of Poland was professor Ignacy Koschembahr-Łyskowski 1864–1945. The author of the article analyzes the overall objectives of the draft of this part of the Code, which was based on a rejection of the idea of individual rights and was difficult to reconcile with the majority of drafts of Codification Committee of the Second Republic of Poland. He indicates that enterprise was placed in the provisions of the general part of the Code relating to legal items, based on a broad concept of legal items and the subject of rights in rem. In the French court judiciary referent Łyskowski noticed a tendency to treat the general relations of monetary value, which a person finds himself, as a property, which could be the subject of property, considered by the doctrine as the universitas iuris. This was to be confirmed also in the Austrian legislation. The referent constructed enterprise as the property of entrepreneur, and as the property which explicitly refers to differentiation of enterprise in civil law, the essence of which could not depend solely on business activities of entrepreneurs and on enterprise in commercial law. The author of the article argues that the legal regulations on civil enterprise included in the analyzed draft were not exhaustive, could sometimes cause problems of interpretation, moreover did not always suit the trends expressed in the legislation of the Second Republic of Poland.
Keywords: general part of the Civil Code; enterprise; universitas iuris; broad notion of legal items and the subject of rights in rem; property